2015
DOI: 10.1007/s00441-015-2199-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression and localization of the diacylglycerol kinase family and of phosphoinositide signaling molecules in adrenal gland

Abstract: Adrenal glands play a central role in the secretion of steroid hormones and catecholamines. Previous studies have revealed that molecules engaged in phosphoinositide (PI) turnover are expressed in the adrenal gland, suggesting the importance of PI signaling in adrenal signal transduction. Diacylglycerol kinase (DGK) catalyzes the phosphorylation of diacylglycerol (DG), a major second messenger in the PI signaling cascade. The DGK family is expressed in distinct patterns in endocrine organs at the mRNA and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 61 publications
2
10
0
Order By: Relevance
“…It is thus likely that DGK⑀ is present in these contact sites, which would locate the protein in a suitable environment to trigger its activity and acyl-chain specificity upon membrane morphological changes, tightly regulating the PI cycle. This proposition is consistent with the observation that in a biological membrane, DGK⑀ is not randomly distributed in the membrane but rather is present in discrete locations close to the PM (60,61). In the basal state, DGK⑀ would have low activity and low acyl-chain specificity, but upon stimulation, the enzyme would be activated at specific sites of the membrane having high negative Gaussian curvature.…”
Section: Membrane Sites Of High Gaussian Curvature Regulate Dgk⑀supporting
confidence: 88%
“…It is thus likely that DGK⑀ is present in these contact sites, which would locate the protein in a suitable environment to trigger its activity and acyl-chain specificity upon membrane morphological changes, tightly regulating the PI cycle. This proposition is consistent with the observation that in a biological membrane, DGK⑀ is not randomly distributed in the membrane but rather is present in discrete locations close to the PM (60,61). In the basal state, DGK⑀ would have low activity and low acyl-chain specificity, but upon stimulation, the enzyme would be activated at specific sites of the membrane having high negative Gaussian curvature.…”
Section: Membrane Sites Of High Gaussian Curvature Regulate Dgk⑀supporting
confidence: 88%
“…The position of size marker is indicated to the left (bp). Hozumi et al, 2015). These findings suggest that DGKζ plays a role in islet cell function.…”
Section: Discussionmentioning
confidence: 82%
“…A prominent feature of the DGK family is that most isozymes are expressed abundantly in the brain, suggesting the physiological importance of this enzyme family for proper brain function (Goto and Kondo 2004;Goto et al, 2006). In addition, recent studies have shown characteristic expressions and localization patterns of DGKs in other organs, including the peripheral nervous system, heart, vascular smooth muscle and endothelial cells, lung, liver, female reproductive organs, pituitary gland, adrenal gland, and retina under pathophysiological conditions (Goto et al, 2007;Nakano et al, 2009;Hozumi et al, 2010;Hozumi and Goto 2012;Nakano et al, 2012;Hozumi et al, 2013;Goto et al, 2014;Hozumi et al, 2015). These observations suggest that the DGK family is involved in widely diverse functions of various tissues and organs.…”
Section: Introductionmentioning
confidence: 99%
“…In adrenal cells, a group of PI signaling molecules are expressed significantly in zona glomerulosa cells and medullary chromaffin cells in the adrenal gland. The same study showed that DGKγ localizes to the Golgi complex, DGKε to the plasma membrane, and DGKζ to the nucleus of adrenal cells [88]. Furthermore, DGKs δ and η localize to endosomes [37,45].…”
Section: Cellular Localization and Distribution Of Dgksmentioning
confidence: 82%
“…In addition, nuclear DGKs ζ and ι localize within distinct nuclear compartments [17,84] whereas DGKα localizes mainly at the nuclear periphery [17,71]. DGKs also localize within other organelles and this may be cell type-specific [87,88]. Localization and expression of DGKs in the brain remain elusive.…”
Section: Cellular Localization and Distribution Of Dgksmentioning
confidence: 99%